Consumo excesivo de sustancias psicoactivas y su incidencia en el trastorno de ansiedad generalizada en una persona de 30 años de edad en el Centro de Privación de Libertad Masculino Bolívar Número Uno - Melendrez Nuñez, Lourdes Karina (2021)
This case study is aimed at knowing and identifying how the excessive consumption of psychoactive substances influences the development of a Generalized Anxiety Disorder in a 30 years old person who is deprived of liberty, in the BOLIVAR NUMBER ONE MALE LIBERTY DEPRIVATION CENTER, in the Guaranda canton, belonging to the Bolívar province, this study consists of the collection of diagnostic information and psychological treatment for generalized anxiety disorder induced by the consumption of various psychoactive substances, for the same it carried out a scheme therapy focused on information exploration techniques typical of the field of clinical psychology, in addition to the use of cognitive behavioral therapy, in which the methodology used to carry out the research focused on the scientific investigation of the variables proposed for this study , which are the excessive consumption of psi substances coercive and anxiety disorder specifically generalized anxiety disorder, for rehabilitation through the use of information gathering techniques, such as psychometric tests, semi-structured interview, medical history, direct observation, and the CIE-10 and DSM diagnostic manual 5, are the main sources of information, together with the personal interview of the patient, the rehabilitation of the same was carried out within the social insertion program proposed by the deprivation of liberty center.